Resistance to Nuclear Waste Disposal: Credentialed Experts, Public Opposition and their Shared Lines of Critique - Durant, Darrin (Scientia Canadensis)

(untitled) (CSTHA/AHSTC, 2007)
AbstractThis article asks the question whether, in regard to controversial technical decision-making, lay public groups advance different kinds of resistance than credentialed experts. This question is explored via a case-study analysis of one of Canada's major public controversies of the past quarter century—nuclear waste disposal. Having arrived on the policy radar in 1977, nuclear waste remained an internal government/nuclear industry matter until terms of reference for a public inquiry were announced in 1989. Several access points for public input followed that announcement: scoping sessions in 1990, comments received during 1994-96 on an Environmental Impact Statement (EIS) prepared by Atomic Energy Canada Limited (AECL), nation-wide public hearings in 1996-97, and ongoing public consultation since 2002. This article focuses on the comments on the EIS, and discusses several lines of shared resistance: the expert judgment of AECL was disputed, the lack of peer review was criticized, accusations of unreliability were made, and general deficiencies in the EIS were attributed to narrow terms of reference and poor institutional culture. This article recommends the use of a dramaturgical approach to technical texts, and reveals the assumptions framing the dualist notion that one can unambiguously separate technical and social criticisms of technical projects.